Assessing R&D Investment Policy in the Indonesian Defense Sector: Towards Long-Term Sustainability - Sarjito, Aris (International Journal of Applied and Advanced Multidisciplinary Research, 2024)
The research examines the current state of research and development (R&D) investment policies in the Indonesian defense sector, focusing on their sustainability and long-term impact. It uses institutional, implementation, network, and innovation diffusion theories and secondary data analysis. The findings reveal institutional influences, challenges in implementation, bureaucratic coordination, and measures to enhance long-term sustainability. Historical, cultural, and regulatory factors influence R&D policies, while limited resources make implementation difficult. The study emphasizes the importance of collaboration between the public and private sectors and continuous monitoring and evaluation. The findings provide recommendations for fostering innovation, overcoming challenges, and ensuring the sector's resilience.